The Effectiveness of English Score Application on Pre-Teaching Activities to Improve Vocabulary Mastery at SMAN 8 Padang - Syahada, Tika; Sari, Senorica Yulia (Journal of English Language Teaching, 2024)
This research is pre-experimental research that is aimed to try out whether the use of the EnglishScore application is effective in improving students’ vocabulary mastery. The population of the research was tenth-grade students at SMAN 8 Padang. The population consists of 339 students who are classified into ten classes. X.E2 was selected as the experimental class through cluster sampling method. This research was conducted over eight meetings during school hours. In order to collect the data, the researcher used multiple-choice test for pre-test and post-test. The test questions based on the two adapted narrative texts. The data analysis result shows that the significant value of the two-tailed paired sample t-test is 0.000 which means that the value of the two-tailed less than 0.05. So, the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. In conclusion, the result of this research proved that the use of EnglishScore application had a good impact in improving students’ vocabulary mastery.